1957
DOI: 10.5254/1.3542742
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Aspects of Reinforcement

Abstract: Hydroxyl free radicals were chemisorbed on to the surface of fully reinforcing carbon blacks by reacting them with an aqueous solution of potassium persulfate or of sodium hypochlorite. Both treatments caused a marked decrease in reinforcing ability, from which it was concluded that free radical interaction between these carbon blacks and rubber is a factor in reinforcement. Bound rubber and swelling index, which were determined for commercial carbon blacks covering the full range of particle size used in rubb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, the mechanical properties of CB–CR/ENR blends increased with increasing CB loading. Watson suggested that at least two different kinds of active sites exist on the surface of CB. One type can react with rubber‐free radical formed during milling.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mechanical properties of CB–CR/ENR blends increased with increasing CB loading. Watson suggested that at least two different kinds of active sites exist on the surface of CB. One type can react with rubber‐free radical formed during milling.…”
Section: Resultsmentioning
confidence: 99%
“…In a 1957 paper, Watson referred to the carbon black reinforcement of elastomers and stated, “Some workers believe that the mechanism is at least partly chemical, whereas others claim that it is entirely physical in nature” [ 41 ]. The same statement can be made today, 64 years later.…”
Section: Structural and Chemical Characteristics Of Carbon Blackmentioning
confidence: 99%